Online Media Coverage of Ghana’s U-20 Team at the 2021 African Youth Championships - Tenkorang, Charles (UniMAC-GIJ, 2021)
The study's major aim was to examine Ghanaian online media coverage of Ghana’s U-20 team’s participation at the African Youth Championship in Mauritania in 2021. The objectives of this study was to assess the nature of online media reporting, analyze the major issues addressed by the media, and investigate the dominant frames used by online media when covering the U-20 team in the tournament. The study followed the quantitative content analysis research design to while sampling a total of 100 news stories published on popular football online website ghanasoccernet.com. The findings of this study show that the U-20 squad was well-covered during the competition, with the majority of the stories focusing on the playing body (players and technical coaching staff), albeit other political problems received considerable attention. Furthermore, the study reveals that web reporting focused on a variety of issues, the most prominent of which was a comprehensive focus on the playing body, with the bulk of stories published on the platform focusing on how the team trained, the tournament's final game, and important players from the Ghanaian squad.
MA Journalism